2010
DOI: 10.1073/pnas.1000489107
|View full text |Cite
|
Sign up to set email alerts
|

A type III-like restriction endonuclease functions as a major barrier to horizontal gene transfer in clinical Staphylococcus aureus strains

Abstract: Staphylococcus aureus is an versatile pathogen that can cause lifethreatening infections. Depending on the clinical setting, up to 50% of S. aureus infections are caused by methicillin-resistant strains (MRSA) that in most cases are resistant to many other antibiotics, making treatment difficult. The emergence of communityacquired MRSA drastically changed the picture by increasing the risk of MRSA infections. Horizontal transfer of genes encoding for antibiotic resistance or virulence factors is a major concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
111
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 43 publications
8
111
2
1
Order By: Relevance
“…This may be particularly relevant for the CC398 lineage. Our sequencing findings clearly indicate that CC398 does not harbor any genes for a type IV RM system similar to those previously described (Corvaglia et al, 2010). In addition, the 296 bp fragment of the sauI-hsdSI gene, a reliable discriminative marker of S. aureus CC398 (Stegger et al, 2011), is present and strictly conserved in our isolates.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This may be particularly relevant for the CC398 lineage. Our sequencing findings clearly indicate that CC398 does not harbor any genes for a type IV RM system similar to those previously described (Corvaglia et al, 2010). In addition, the 296 bp fragment of the sauI-hsdSI gene, a reliable discriminative marker of S. aureus CC398 (Stegger et al, 2011), is present and strictly conserved in our isolates.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, the 296 bp fragment of the sauI-hsdSI gene, a reliable discriminative marker of S. aureus CC398 (Stegger et al, 2011), is present and strictly conserved in our isolates. However, our transformation and transduction experiments clearly indicate that the presence of this sauIhsdSI gene, a component of a type I RM system, is not associated with protection against uptake of foreign DNA (Waldron and Lindsay, 2006;Corvaglia et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…However, it is not in agreement with the observation that pairs of genomes encoding cognate R-M systems coexchange more DNA. It is also hardly reconcilable with the notorious deleterious effect of R-M systems on bacterial genetic transformation in the laboratory (35). Although R-M systems have been shown to favor intragenomic HR events (12), the overall effect of R-M systems on genetic exchange is to decrease both HR and HGT between bacteria encoding noncognate R-M systems.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, type I gene complexes appear to function in controlling the evolution of S. aureus strains. Recent studies of type III-like enzymes also revealed the role of these REases as a major barrier to HGT in clinical strains of methicillin-resistant S. aureus (115). Strains deficient in these enzymes were hypersusceptible to the horizontal acquisition of DNA from other species, such as E. coli, and could easily acquire a vancomycin resistance gene from enterococci (115).…”
Section: Immigration Control Maintenance Of Species Identity and Comentioning
confidence: 99%
“…Recent studies of type III-like enzymes also revealed the role of these REases as a major barrier to HGT in clinical strains of methicillin-resistant S. aureus (115). Strains deficient in these enzymes were hypersusceptible to the horizontal acquisition of DNA from other species, such as E. coli, and could easily acquire a vancomycin resistance gene from enterococci (115). Subsequent studies, however, indicated that the type III-like enzyme is actually a type IV REase recognizing 5-methylcytosine/5-hydroxymethyl cytosine-modified DNA (116).…”
Section: Immigration Control Maintenance Of Species Identity and Comentioning
confidence: 99%